Oman äidinkielen tekstitaidot monikielisyyttä rakentamassa – näkökulmia kielille annettuihin merkityksiin ja kielten käyttöön - Tarnanen, Mirja; Kauppinen, Merja; Ylämäki, Annika (AFinLAn vuosikirja, 2017)
This article examines L1 literacy practices and use of L1 from the perspective of students and teachers with migrant background. We focus particularly on the meaning making of literacy practices and use of L1 in both in-school and out-of-school contexts. The data consist of 13 teacher interviews and 10 student interviews and applied tasks completed by the students studying in a comprehensive school. First, we discuss multilingualism and the use of languages in the conceptual framework of translanguaging and literacy practices. Then we introduce the data and the methods. The findings show that multilingualism is present both in students’ everyday lives and to some extent in L1 instruction, but the use of L1 and multilingual literacy practices across the curriculum do not appear to be frequent. Finally, we discuss some implications concerning the multilingualism of students with migrant backgrounds and the role of L1 in their lives. We also consider how L1 instruction supports the development of literacy practices in in-school and out-of school contexts and how L1 instruction could be developed.
Keywords: oma äidinkieli; oman äidinkielen opetus; kielten limittäinen käyttö; monikielisyys; tekstitaidot